Anatomía de la madera de ocho especies de Quercus (FAGACEAE) de Oaxaca, México - de la Paz Pérez Olvera, Carmen; Vélez Jiménez, Susana; Ceja Romero, Jacqueline (Instituto de Ecología, A.C., 2016)
The macroscopic and microscopic anatomical description of the wood of eight species of Quercus from Oaxaca are presented: Q. affinis Scheidw., Q. conzatti Trel., Q. laurina Humb. & Bonpl., Q. scytophylla Liebm. of the section Lobatae (red oaks) and Q. glabrescens Benth., Q. obtusata Humb. & Bonpl., Q. peduncularis Née y Q. rugosa Née of the section Quercus ( white oaks). One tree per species was recolected in the Capulalpam de Méndez and San Pedro Yolox municipalities of the Oaxaca State. The macroscopic study was made in wood samples of 12 cm x 7 cm x 1 cm and for the microscopic study slides of dissociated material and cuts were used. The material was obtained from logs of 1,30 m length which were cut from the base to the crown. Samples of wood and slides showing the typical planes of wood were made. For the quantitative elements an univariate statistic analysis was carried out. On their turn, these were classified on the basis of average values. Differences in wood color, type of porosity, size and distribution of pores, abundance of multiseriate rays size and cellular contents (crystals, gums and tylosis) between the species of both subgenus were observed.